Evolution of beverage portion sizes consumed in Brazil between 2008 and 2018 - Cavalcante, Jessica Brito; Vasconcelos, Thais Meirelles de; Sichieri, Rosely; Bezerra, Ilana Nogueira (Frontiers in Public Health, 2023)
Objective: To describe the evolution of beverage portion sizes consumed in Brazil between 2008 and 2018. Methods: Food consumption data from 2008-2009 and 2017-2018 were used to group beverages according to nutritional characteristics, type and size of portions into eight groups: high-calorie soft drinks, fruit refreshments, alcoholic beverages, coffee/ tea, fruit juices, milk and milk replacers and ultra-processed milk-based beverages. For the analysis of the consumed portions, the two-day food record and recall were considered. All analyses were performed using SAS software version 9.1.3. Results:There was a decrease in the frequency of consumption of beverages between 2008 and 2018 in Brazil. However, between 2008 and 2018, the average portion consumed showed a significant increase for the group of alcoholic beverages (29%), flavored juices (11%), caloric soft drinks (8%), milk and milk substitutes (6 %) and fruit juices (5%); and reduction for the coffee/tea group (11%). Conclusion: The present study presents an initial assessment of the evolution of the beverage portion sizes consumed in Brazil, showing changes in the way the population has been consuming these items over the analyzed period. Individuals have been drinking less frequently, but in larger quantities at the time of consumption.